2007
DOI: 10.1111/j.1540-8159.2007.00656.x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Conversion from Paroxysmal to Permanent Atrial Fibrillation

Abstract: Our results show that a P-SAECG, an analysis of CHRS, and left atrial enlargement are clinical predictors of a progression from PAF to PEAF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 27 publications
(98 reference statements)
2
15
0
Order By: Relevance
“…In this study, during an average follow-up period of 28 (23) months, eight patients (21.6%) with non-valvular PAF developed CAF. The probability of progression to CAF (permanent AF) has been reported to be about 8.6% after 1 year, 21% after 2 years and 24.7% after 5 years in PAF patients, which is consistent with our results made on a standard ECG or 24 h Holter ECG,4 31 though such a 7-day Holter ECG would have been a more robust method, if possible in our patients. Several echocardiographic and electrocardiographic parameters were investigated as predictors of AF, but it still remains difficult to predict progression from PAF to CAF 49…”
Section: Discussionsupporting
confidence: 92%
“…In this study, during an average follow-up period of 28 (23) months, eight patients (21.6%) with non-valvular PAF developed CAF. The probability of progression to CAF (permanent AF) has been reported to be about 8.6% after 1 year, 21% after 2 years and 24.7% after 5 years in PAF patients, which is consistent with our results made on a standard ECG or 24 h Holter ECG,4 31 though such a 7-day Holter ECG would have been a more robust method, if possible in our patients. Several echocardiographic and electrocardiographic parameters were investigated as predictors of AF, but it still remains difficult to predict progression from PAF to CAF 49…”
Section: Discussionsupporting
confidence: 92%
“…24,25 On the basis of the general concept that an enlarged atria causes broad P-waves on a standard ECG, several studies have focused on the influence of atrial size on the P-wave duration in patients with or without AF, but the results are conflicting. Budeus et al have reported a significant positive correlation between FPD and atrial size (r=0.57, P=0.001) in patients with paroxysmal AF, 26 whereas Ishimoto et al did not observe a significant correlation between FPD and atrial volume, which was measured by cine magnetic resonance imaging, in patients with paroxysmal AF. 23 Chalfoun et al demonstrated a strong correlation between FPD and atrial size in patients who remained in sinus rhythm (R 2 = 0.67, P=0.003), but not in those who returned to AF (R 2 = 0.11, P=0.65) after electrical cardioversion for persistent AF, and they suggested that the lack of correlation between atrial size and FPD in those who reverted back to AF might be related to electromechanical dissociation in their atria.…”
Section: Discussionmentioning
confidence: 94%
“…Applications of SAECG are similar to P wave indices’ described above. Prolonged P wave SAECGs have been associated with recurrence of AF following cardioversion;50 comparison of hypertensive subjects with paroxysmal AF and those without;51 AF following cardiothoracic surgery;52;53 and transition from paroxysmal to permanent AF 54. Advantages of SAECG include its incorporation of information from hundreds of data points and lack of reliance on distinguishing P wave on-set and off-set, which improve the reliability and accuracy of the technique.…”
Section: Signal Average Ecgmentioning
confidence: 99%